(3QSGdI GdCfhGQ aj JMbjb ebGe GdTjN CMeO Hf CMeO Gdejehfjs - (3eLghds
(3ChdgG (B:s
(3HfaSj NGWQJ hd`hYde`J CfgG UYHI ceG TgOJ dNVJ WQbG UgdI GdeSGdc hLfHJ GdYWH hGdegGdc s
(3BNQgG (B:s
(3hbO Mci CfG WGdHkG MVQ eLdS OQSg, aGNJda eY TjNg GdeOQS aj ehJ GdEeGe eGdc Hf CfS, hehJ eSde Hf MLGL, CjgeG SHb GdBNQ HGdhaGI s
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B194 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs